Measurement of invertase, maltase and β-galactosidase activities on small samples of intestinal mucosa - Ciliv, Gönenc; Özand, Pınar (The Turkish Journal of Pediatrics, 1965)
A micro method for the determination of invertase, maltase, and lactase is described.